Casting a Critical Lens on Thailand’s Higher Education System: A Case Study of Women’s Experiences as Agricultural Extension Faculty - Morgan A. Richardson Gilley; Richie Roberts; Kristin Stair; J. Joey Blackburn (Journal of International Agricultural and Extension Education, 2023)
The agricultural industry and higher education have traditionally been male-dominated spaces in the developing world. However, in recent decades, significant progress in female representation has been achieved in both sectors. Previous research has suggested that women in the Southeast Asian agricultural industry have been more empowered than women in other regions. However, women in Thailand’s agricultural postsecondary programs have been understudied. In response, this study examined the experiences and perceptions of women agricultural extension faculty in Thailand’s higher education system. Through qualitative analysis of in-depth interviews with women, three distinct themes emerged: (1) gendered disparities, (2) barriers to success in academia, (3) perceptions of self and gender in agriculture and higher education. The findings suggested that Thai female faculty in agricultural extension held positive perceptions of their careers despite persistent gender inequalities and traditional cultural norms. Moving forward, we recommend that more in-depth research be conducted to understand better how such perceptions coexist with the deeply entrenched gender inequalities.
Keywords: extension; feminism; higher education; power dynamics; Thailand; women